Integration of Local Wisdom and Organizational Support in Strengthening Lecturers’ Professional Commitment Through A POP-SDM Approach - Anjaswuri, Fitri; Hardhienata, Soewarto; Suhendra, Suhendra (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to analyze the influence of local wisdom and organizational support on lecturers’ professional commitment in private higher education institutions in Bogor, both directly and indirectly through work motivation and religiosity. The study employs a quantitative approach with an explanatory research design. Primary data were collected through a Likert-scale questionnaire distributed to 150 lecturers from a population of 960 using proportionate random sampling, while secondary data were obtained from institutional documents and relevant literature. The research was conducted at three private universities in Bogor. Data analysis was performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that local wisdom and organizational support have significant effects on lecturers’ professional commitment, both directly and indirectly through work motivation as a mediating variable. Religiosity has a significant effect on professional commitment but not on work motivation. The model demonstrates an acceptable level of fit and moderate predictive power. The findings conclude that integrating local wisdom values and organizational support is an effective strategy for enhancing lecturers’ professional commitment in a sustainable manner.